IMPROVEMENT OF MARKETING RESEARCH IN OIL PRODUCTION ENTERPRISES - Khalikova Malika Mamurdjanovna (Journal Park Publishing, 2022)
In this article, the theoretical and methodological foundations of marketing research in oil production enterprises are studied, and the author comments on the regional analysis and segmentation of the market. The author presented scientific proposals and recommendations on the development of a marketing strategy for the formation of marketing research in oil production enterprises.
Keywords: Roadmap, regional analysis, segmentation, oil production, marketing research.